Toxic and genotoxic potential evaluation of soil samples by bioassays - Lah Jarc, Barbara (Acta agriculturae Slovenica, 2005)
Soil samples were obtained from Slovenian industrial region Šaleska dolina and aqueous leachates were prepared. The toxicity and genotoxicity potential of these aqueous fractions have been evaluated by in vitro toxicity and genotoxicity bioassays. Freshwater toxicity test (PROTOXKIT FTM) with a ciliate protozoan Tetrahymena thermophila, and genotoxicity comet assay using Tetrahymena thermophila, Caco-2 and HepG2 cell lines were performed. Biological data were completed through chemical analyses. It has been shown that physico-chemical analyses alone may not be sufficient to characterize soil hazards. To study soil ecotoxcity it is therefore necessary to take into consideration both, the physico-chemical analyses, toxicity and genotoxicity assays.
Keywords: microbiology; mikrobiologija; genotoksičnost; toksičnost; vzorci zemlje; biotesti; Slovenia; Slovenija